Serological markers of HBV infection: A community-based study of urban dwellers in Southwest Nigeria (2020)
Background and Aim: Globally, hepatitis B virus (HBV) infection has been a major public health issue. In sub-Saharan Africa, about 10–20% of the general population are chronic carriers of HBV infection, making it a high endemic region. This study was designed to evaluate the pattern of distribution of markers of HBV among asymptomatic subjects in an urban community in southwest Nigeria. Methodology: The study was carried out among apparently healthy subjects without prior knowledge of their HBV status. A structured questionnaire was used to collect demographic and relevant information, while ELISA kits were used to detect HBsAg/Ab, HBeAg/Ab, Total anti-HBc, and anti-HBc IgM using the participants’ sera. Results: The results of 438 subjects comprising 133 (30.4%) males and 305 (69.6%) females were analysed, age ranged 1.5–70 years (35.7 ± 15.7 years). Overall, 31 (7.1%) of the participants had detectable HBsAg, 2 (6.5%) and 7 (1.6%) subjects had detectable HBeAg and anti-HBc IgM respectively. Anti-HBs was detected in 83 (18.9%) subjects, while 39 (8.9%) had anti-HBe. Of the HBsAg positive participants, 13 (3.2%) were also positive for both anti-HBc IgM and HBeAg, 25 (80.6%) had anti-HBe, while 3 (9.7%) had only anti-HBc IgM. None of them had anti-HBs. Among those who were HBsAg negative, 83 (20.4%) had anti-HBs as the only serological marker, while 313 (76.9%) had no serological markers of HBV infection. Only 145 of the total population were tested for anti-HBc Total, of whom 65 (44.8%) were positive. Conclusion: This study has highlighted the burden of HBV infection in the population studied. There is therefore the need for more awareness through information programmes to the public and for preventive measures through vaccination programmes.